Fokus Penelitian Berpikir Kritis Siswa dalam Pembelajaran Ekonomi: Bibliometrik Analisis 2019-2023 - Triansyah, Fadli Agus; Suwatno, Suwatno; Supardi, Endang (Universitas Nusantara PGRI Kediri, 2023)
Critical thinking is understanding, analyzing, evaluating information, and making reasoned and rational decisions. This ability is one of the essential skills for students in solving problems and making decisions in everyday life. The purpose of this study is to identify publications related to critical thinking in economics learning and to describe the characteristics of this research. The bibliometric analysis method was used in this study. The research results show that the number of publications related to critical thinking in economics studies will increase yearly from 2019 to 2023. Meanwhile, the most significant number of documents come from Indonesia. OSF Preprints holds the top position as an institution or publisher with 14 papers. At the same time, the author with the most citations is Abbas with 17 citations, followed by Aslamiah with 17 citations, and Fitriyah with ten citations. New themes emerging in this field are